Comparison of Antioxidant Compounds between Glycine max and Bos taurus milk - Izz Nurryn Mohd Riza; Nur Adlin Wahida Murad; Liyana Amalina Adnan (USIM Press, 2024)
MJoSHT2020, Volume 7, Special Issue, eISSN: 2601-0003